Makna Frasa “Gambar dan Rupa” dalam Kejadian 1:26 - Timotius, Han; Setyarini, Lilis; Stella, Yunita (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2025)
This study discusses the phrase “image and likeness” in Genesis 1:26, which has caused much debate regarding the creation of man from the perspective of theologians and lay Christians. Genesis 1:26 is conflated with Genesis 5:1-3, as well as the appearance of the conjunction “and” in Genesis 1:26 which is not found in the original Hebrew text. In addition, practices such as the marriage of humans with animals and humans with objects further damage the image of God in humans. The purpose of this study is to provide a proper explanation of the true meaning of the phrase “image and likeness” in man. The method used is qualitative exegesis with eight steps of analysis: grammatical, lexical, textual, contextual (near and far context), structural, historical, theological, and exegetical. The results show that the addition of the conjunction “and” is a mistake, because in the Hebrew text there is no conjunction ? (we) which makes it seem as if the two words have different meanings, and that humans as the image and representative of God in the world must display God's authority. In conclusion, “image” and “likeness” have the same meaning; and man as the image of God must display authority and have dignity that is different from the rest of creation.